What have we learned? Problem-solving capacity of the multilevel European polity - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2001)
This Working Paper is an attempt, occasioned by the evaluation of the Max Planck Institute for the Study of Societies, to provide a conceptual framework within which institute research on multi-level European problem solving could be discussed in the context of a more comprehensive overview of the literature. The framework combines an institutional dimension (distinguishing between supranational, joint-decision and intergovernmental modes of EU policy making) and a policy dimension (distinguishing between market-creating, market-enabling, market-correcting and redistributive policies). As institutional modes differ in their capacity for conflict resolution, and as policy types differ in the likelihood of severe policy conflict, greater or lesser problem-solving capacity can be explained by the location of a particular policy area on both of these dimensions. – – Aus Anlass der Evaluierung des Max-Planck-Instituts für Gesellschaftsforschung entwickelt dieses Working Paper einen Bezugsrahmen, in dem die Ergebnisse der am Institut betriebenen Forschung zur europäischen Mehrebenenpolitik im Kontext der internationalen Literatur eingeordnet und diskutiert werden können. Der Bezugsrahmen verbindet eine institutionelle Dimension (in der zwischen supranationalen, verflochtenen und intergouvernementalen Interaktionsformen unterschieden wird) mit einer Policy-Dimension (in der zwischen marktschaffenden, marktfördernden, markt-korrigierenden und redistributiven Policy-Typen unterschieden wird). Da Interaktionsformen sich in ihrer Konfliktregelungskapazität, und da Policy-Typen sich in ihrer Konfliktwahrscheinlichkeit unterscheiden, kann die größere oder geringere Problemlösungsfähigkeit in einem bestimmten Politikfeld durch dessen Lage in beiden Dimensionen erklärt werden.
Keywords: 300